Therapeutic Potential of Arctium lappa L. Root Extracts to Inhibit Gastrointestinal Bacterial Pathogens and Treat Gastrointestinal Disease - Mingji, Cheng; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: An increase in antibiotic resistance and a corresponding decrease in antimicrobial discovery have directed researchers towards alternative therapies, including plant based medicines. However, synergistic combinations of plant extracts with conventional antibiotics may be a far more effective approach in overcoming resistance and potentiating the activity of antibiotics that are otherwise ineffective against resistant bacterial strains. Materials and Methods: The antibacterial activity of Arctium lappa L. root extracts was investigated by disc diffusion and quantified by liquid dilution and solid phase MIC assays. The extracts were also combined with a range of conventional antibiotics and tested against various microbial triggers of autoimmune diseases. The ΣFIC values obtained from these assays were used to determine the class of combinational effects. Toxicity was evaluated by Artemia nauplii mortality and HDF cytotoxicity assays. Results: Methanolic and ethyl acetate A. lappa root extracts showed good inhibitory activity against several gastrointestinal bacterial pathogens. They were particularly good inhibitors of S. sonneii and B. cereus, with MIC values in the range 150-250μg/mL. The aqueous extract was also a noteworthy inhibitor of B. cereus growth. Of further interest, some combinations of the A. lappa root extracts and conventional antibiotics potentiated bacterial growth inhibition compared to the individual components. Four synergistic and five additive interactions were noted. Notably, no antagonistic interactions were evident, indicating that all combinations could be used without decreasing the antibacterial activity of the components. All extracts were non-toxic in the ALA and HDF assays. Conclusion: Arctium lappa root extracts have potential as inhibitors of bacterial gastrointestinal pathogens. Furthermore, extract components may also potentiate the activity of some antibiotics that are relatively ineffective alone. Isolation and identification of these compounds may be beneficial in drug design against several gastrointestinal bacterial pathogens.
Keywords: Burdock root; Synergy; Conventional antimicrobials; Interaction; Medicinal plants; Diarrhoea; Gastrointestinal pathogens; Drug combinations